Stroke related brain-heart crosstalk: pathophysiology, clinical implications, and underlying mechanisms - Fan, Xuehui; Cao, Jianyang; Li, Mingxia; Zhang, Dechou; El-Battrawy, Ibrahim; Chen, Guiquan; Zhou, Xiao-Bo; Yang, Guoqiang; Akın, Ibrahim (Advanced science, 2024)
The emergence of acute ischemic stroke (AIS) induced cardiovascular dysfunctions as a bidirectional interaction has gained paramount importance in understanding the intricate relationship between the brain and heart. Post AIS, the ensuing cardiovascular dysfunctions encompass a spectrum of complications, including heart attack, congestive heart failure, systolic or diastolic dysfunction, arrhythmias, electrocardiographic anomalies, hemodynamic instability, cardiac arrest, among others, all of which are correlated with adverse outcomes and mortality. Mounting evidence underscores the intimate crosstalk between the heart and the brain, facilitated by intricate physiological and neurohumoral complex networks. The primary pathophysiological mechanisms contributing to these severe cardiac complications involve the hypothalamic-pituitary-adrenal (HPA) axis, sympathetic and parasympathetic hyperactivity, immune and inflammatory responses, and gut dysbiosis, collectively shaping the stroke-related brain-heart axis. Ongoing research endeavors are concentrated on devising strategies to prevent AIS-induced cardiovascular dysfunctions. Notably, labetalol, nicardipine, and nitroprusside are recommended for hypertension control, while β-blockers are employed to avert chronic remodeling and address arrhythmias. However, despite these therapeutic interventions, therapeutic targets remain elusive, necessitating further investigations into this complex challenge. This review aims to delineate the state-of-the-art pathophysiological mechanisms in AIS through preclinical and clinical research, unraveling their intricate interplay within the brain-heart axis, and offering pragmatic suggestions for managing AIS-induced cardiovascular dysfunctions.
Zuerst veröffentlicht: 2. Februar 2024
Gesehen am 07.06.2024